The Claim to "Hidden Truths" as the Reason for the Rejection of Kabbalah by the Wissenschaft des Judentums - Kohler, George Y. (Jewish Thought, 2020)
The essay analyses several reasons for the well-known rejection of the theological "worth" of kabbalah by two of the leading scholars of the 19th century German-Jewish movement of Wissenschaft des Judentums: Heinrich Graetz and Abraham Geiger. Kabbalistic esotericism, resting on fraudulent claims to authorship and masking the irrationality of its doctrines, was among the major objections of these historians. Dealing in mysticism was understood to ruin the morality of human relations by leading to a secretive, elitist individualism instead of creating a healthy human society —- kabbalah focused on the capturing of imaginary worlds instead of improving the existing world. Particularly disturbing was that kabbalah often blurred the boundary between the bodily and the spiritual, specifically by formulating a new, hallowed dialectic relation between human limbs and the human intellect that was purportedly superior to common morality. Eventually, both scholars agreed that kabbalah could therefore not promote the modern Judaism that nineteenth-century German Jews wished to see as a viable, ethical alternative to traditional religion, a Judaism that is capable of survival in the modern age. We may define science as the analysis and explanation of the laws of nature, as well as the rules that govern human society and history, with results that lay open this research’s methodology and allow the scientific outcome to be reproduced. Given this definition, science in essence becomes the ultimate disclosure of all secrets. Esotericism anchored in revelation or a purported authoritative tradition that can be known only by the initiate thus stands in contradiction to scientific research. The kabbalist, who speaks of “hidden truths” which he believes to be universally true but not in need of or even open to rational proof, is not only being irrational from a scientific perspective but also falsely pretentious. The present study will look into the exciting question of what happened when these two methods of knowledge, the scientific and the kabbalistic, came for the first time in close contact within the realm of Judaism.